Hubungan Pola Asuh Orang Tua Terhadap Prestasi Belajar Siswa Kelas V Madrasah Ibtidaiyah At-Taqwa 51 Kota Bekasi - Nurul Qisthi; Henri Peranginangin Tanjung; Moh. Mas'ud Arifin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This research discusses the relationship between parenting style and learning achievement of fifth grade at Madrasah Ibtidaiyah At-Taqwa 51 Bekasi. Based on observations, some grade V at Madrasah Ibtidaiyah At-Taqwa 51 Bekasi have low academic achievement. This is indicated by the presence of students who are still late for school and when a teacher gives homework (PR) there are some students who do not work on it and during daily tests and semester tests some students get score below the Minimum Completeness Criteria (KKM), so that a re-examination must be carried out to achieve the KKM score. The purpose of this research was to obtain data about the relationship between parenting parents and the learning achievement of fifth grade at Madrasah Ibtidaiyah At-Taqwa 51 Bekasi. The research method used is a quantitative correlation approach with observation techniques and distributing questionnaires to fifth grade at Madrasah Ibtidaiyah At-Taqwa 51 Bekasi, academic year 2022/2023, totaling 45 respondents. The results showed that the value of Alpha Sig. 0.000 <0.05, which is equal to 0.011 <0.05 or with the test results using rcount > rtable, which is equal to 0.375 > 0.301 so that Ha failed to reject and H0 was rejected. In conclusion, there is a significant relationship between parenting style and learning achievement of fifth grade at Madrasah Ibtidaiyah At-Taqwa 51 Bekasi with a correlation of 14.1%. The permissive type of parenting is the parenting style most widely applied by parents of fifth grade students compared to democratic and authoritarian parenting styles.